Tumor-reactive TCRs within exhausted TILs reveal cancer type-specific immune landscapes in renal cell carcinoma - Komahashi, Mitsuru; Horaguchi, Shun; Tsuji, Kayoko; Hoshino, Daisuke; Kishida, Takeshi; Usui, Kimitsugu; Nakaigawa, Noboru; Sato, Shinya; Hamana, Hiroshi; Kishi, Hiroyuki; Wei, Feifei; Mano, Yasunobu; et al. (Frontiers in Immunology, 2026)
Clear cell renal cell carcinoma (ccRCC) presents a unique immunological paradox: abundant CD8+ tumor-infiltrating lymphocytes (TILs) correlate with poor prognosis. To clarify their functional status and therapeutic potential, we performed single-cell transcriptomic profiling of TILs from 15 patients with ccRCC and functionally validated dominant T cell receptor (TCR) clonotypes using autologous tumor-derived organoids. Single-cell RNA sequencing revealed dynamic shifts in T cell composition, with effector and progenitor-exhausted CD8+ T cells declining and terminally exhausted CD8+ and regulatory CD4+ T cells enriched in advanced tumors. Despite this exhausted phenotype, in an exploratory analysis with five patients, approximately half of the top 20 TCR clonotypes retained anti-tumor reactivity when re-expressed in non-exhausted T cells, as evidenced by TCR-T cell-mediated cytotoxicity and IFN-γ production against autologous organoids. Transcriptomic signatures enabled the development of a penalized logistic regression classifier that distinguished tumor-reactive from bystander T cells with high accuracy, with AUCs of 0.903 (training) and 0.913 (test). Cross-cancer comparison with pancreatic ductal adenocarcinoma (PDAC) datasets revealed limited generalizability, highlighting the need for cancer type-specific models. Notably, ccRCC-specific TILs exhibited mature, functionally differentiated profiles with limited proliferation, consistent with chronic antigen exposure, whereas PDAC-reactive TILs showed highly proliferative and activated phenotypes indicative of ongoing clonal expansion. Collectively, these findings suggest key features of the immune landscape in ccRCC and provide a preliminary, proof-of-concept transcriptomic framework for prioritizing candidate tumor-reactive TCRs. These insights suggest the feasibility of identifying candidate TCRs for future development of TCR-based adoptive T cell therapies in ccRCC and emphasize the importance of integrating single-cell profiling with functional analyses to refine immunotherapeutic strategies. Given the limited sample size, our results should be considered exploratory and hypothesis-generating, and future studies will be required to validate these findings in larger, independent ccRCC cohorts.